What do we know about the future of water in food systems? - Ringler, Claudia; McCartney, Matthew P.; Hafeez, Mohsin (International Food Policy Research Institute, 2025)
Demand is growing while supply is uncertain: Globally, the demand for water in agriculture and food systems is growing, alongside competing needs in other sectors. Freshwater consumption is projected to increase by 17 percent between 2020 and 2050, most of it for irrigation, and almost all of it in low- and middle-income countries. At the same time, water availability is becoming increasingly uncertain due to climate extremes, long-term climate change, pollution, and land use changes such as deforestation and wetland degradation. The rising variability and scarcity contribute to competition among different water users.